De la classe d’accueil à la classe ordinaire : une expérience de « bien-être » ? Étude qualitative auprès d’élèves de l’enseignement secondaire vaudois (Suisse) - Stéphanie Bauer; Nadine Aebischer; Rachel Ribet (Recherches en Éducation)
Committed to the development of an inclusive school, the canton of Vaud encounters certain difficulties in being able to equitably ensure the success of all its students, and in particular that of newcomer students. This qualitative study addresses the schooling experience of newcomer students who attended an immersion class in secondary 1. The well-being model is used and defined through the satisfaction of three needs: relationship, competence and autonomy. Semi-directive interviews were used with students from 14 to 17. The results show the importance of socialization between peers, the mediating role of French language on the feeling of competence and an autonomy limited by the school structure, thus illustrating a mitigated well-being experience. The latter is indeed hampered by the logic of orientation and selection inherent of the canton’s secondary system, thus revealing significant obstacles in the development of the inclusive school